Inventarisasi Jamur Terbawa Benih Cabai Dari Desa Sidodadi Ramunia, Deli Serdang Sumatera Utara - Sukapiring, Dewi Novina (Konservasi Hayati, 2024)
Inventory of seed-borne fungi is a data collection on fungi that infect seeds, this is done to determine the health of the seeds. Seed health testing is very necessary to prevent the spread of disease in the field through seeds. The aim of this research is to inventory and identify fungi carried by chili seeds from Sidodadi Ramunia village. The research method used was isolation of seed-borne fungi which refers to seed health testing methods, namely the Blotter Test method, Rolling Paper method and identification of the fungi obtained to determine the type of fungi that infects chili seeds. The results obtained were that chili seeds from Sidodadi Ramunia Village were infected with seed-borne fungi with the highest percentage being 8% and the lowest being 0.5%. The seed-borne fungi with the highest percentage of infection is the fungus Curvularia sp. The conclusion of this research is that red chili seeds from Sidodadi Ramunia Village, Deli Serdang, North Sumatra were infected with seed-borne fungi, namely Aspergillus sp1., Fusarium sp., Curvularia sp., and Aspergillus sp2. Next, it is necessary to carry out pathogenicity tests and molecular identification of the fungi that have been identified.